Students’ Translation Techniques and Grammatical Errors in Translating Narrative Text - Wahyono, Muhammad Ichsan Andi; Yuliasri, Issy (ELT Forum: Journal of English Language Teaching, 2019)
This research attempted to find out the translation techniques and grammatical errors in students’ Indonesian-English text translation. The objectives of this research were to describe the choice of translation techniques and grammatical errors of the students’ translation of a narrative text. This research used descriptive qualitative method. The translation techniques analysis was done by using Molina and Albir's (2002) classification of translation techniques while grammatical errors of the students’ translation were analyzed using the guide for correcting writing errors by Betty Azar (1941). The translation technique analysis was done by comparing the students’ translation work with the source text of a narrative entitled Lari Kepagian then grammatical errors analysis was done to find out their errors in the use of grammatical rules. The result of the study found that there were 3012 data of translation techniques and 429 grammatical errors. The data showed that the most used translation techniques were literal translation technique (30.1%) and modulation technique (22.6%) and the most grammatical errors made was capitalization (18.2%) and verb tense (16.6%). The most used translation technique that resulted in most grammatical errors was modulation technique (17%) in the translation done by 24 students. Keywords: translation; translation techniques; students’ translation; grammar; grammatical errors; narrative text